PENGARUH AKTIVITAS LALU LINTAS TERHADAP TINGKAT KEBISINGAN SEKITAR TEMPAT IBADAH DI KECAMATAN PADANG BARAT (STUDI KASUS: MASJID MUJAHIDIN, MASJID TAQWA MUHAMMADIYAH - Sri Mutia; Deded Chandra (JURNAL BUANA, 2023)
The purpose of this study is to find out how the noise level is also to know how traffic activity influences the noise level around the Mujahidin Mosque and the Taqwa Muhammadiyah Mosque. This research is a quantitative descriptive research. Field noise measurement data was spatially interpolated using the geostatistical interpolation analysis feature in ArcGis 10.3 software. The results of the research on traffic noise around the Mujahidin Mosque on weekdays are highest in the afternoon around 68.0 dBA. While the Taqwa Mosque on weekdays is highest in the morning around 78.3 dBA. On holidays the Mujahidin Mosque has the highest noise in the afternoon around 80.1 dBA. Meanwhile, the noise at the Taqwa Mosque is highest in the afternoon and evening, around 66.8 dBA. The number of vehicles passing around the study site has a relevant effect on the noise level obtained.